Carbon Structures and Tribological Properties of Fe-C-SiC Self-Lubricating Metal Matrix Composites Prepared with α/β-SiC Polytypes - Guilherme Oliveira Neves; Diego Berti Salvaro; Tatiana Bendo; Deise Rebelo Consoni; José Daniel Biasoli de Mello; Cristiano Binder; Aloisio Nelmo Klein (Lubricants, 2022)
Sintered iron-based self-lubricant composites in which graphite reservoirs are generated by the dissociation of silicon carbide (SiC) particles feature low friction coefficients and scuffing resistance combined with high mechanical stress. This work evaluated the influence of the sintering temperature and the SiC polytype on the graphite reservoirs morphology, structure, and friction behaviour. The reservoirs were studied by field emission gun-scanning electron microscopy (FEG-SEM), micro-Raman spectroscopy, and transmission electron microscopy (TEM). The friction behaviour was evaluated by cylinder on plane tests (friction coefficient and scuffing resistance). The results showed that the SiC polytype and the sintering temperature modified the graphite structures. The SiC dissociation promoted the formation of different nano graphites, presenting different turbostratic 2D and 3D arrays. The results showed that the presence of the turbostratic graphite was beneficial to the friction behaviour of these composites, which offered better tribological performance than the composite with 3D graphite.